Preconceito flagrante e sutil frente à esquizofrenia: explicações com base em crenças causais e estereótipos - Melo, Juliana Rízia Félix de (2017)
Prejudice against schizophrenia is a present phenomenon rooted in society. The most current studies in the area of prejudice show that it no longer occurs blatantly but has taken on more subtle forms of manifestation. Aiming at this, we propose a model of flagrant prejudice and subtle prejudice to the context of schizophrenia, indicating stereotypes and causal beliefs as explanatory variables. Three quantitative and descriptive studies were performed to reach this goal. The first one aimed at constructing and validating the scales of perception of inadequacy to the standard of normality, exaggeration of group differences and benevolence; In addition to adapting the scales of perceived threat to the mentally ill and the social distance scale facing the mentally ill. The sample had 200 students from public and private universities in cities of Paraíba, with a mean age of 25.31 years (SD = 7.21). The data were analyzed through SPSS, in which exploratory factorial analyzes were performed. The scales presented good psychometric indexes with Cronbach's Alpha ranging from 0.62 to 0.84. In order to carry out a confirmatory analysis of the structure of these measures, the second study was carried out with 200 students from public and private universities in Paraíba, with a mean age of 24.82 years (SD = 6.97). For the data analysis we resorted to AMOS program, which was used to perform confirmatory factorial analyzes, adopting the MLE (Maximum Likelihood estimator). The results of the confirmatory factorial analyzes allowed to confirm the factorial structure of the scales, which presented satisfactory adjustment indices. Considering the suitability of the proposed scales, the third study was carried out to test the model of flagrant and subtle prejudice indicating the stereotypes and causal beliefs that explain these two types of prejudice. For this, 200 students from public and private universities in Paraíba cities with a mean age of 29.1 years (SD = 8.52) were enrolled. The five scales validated in studies 1 and 2, as well as a stereotype scale against schizophrenia and one of causal beliefs about mental illness were used as instruments. Descriptive and inferential statistical analyzes were carried out through SPSS and confirmed through AMOS. It was verified that the model with two correlated factors denominated Flagrant Prejudice (gathering the dimensions: Perception of threat and Rejection to relations of intimacy) and Subtle Prejudice (grouping the dimensions: benevolence, perception of inadequacy and exaggeration of group differences) was the model that presented the best indexes of adjustment when compared with other six alternative models [χ² (18) = 61,03, p < 0,05; χ²/gl = 3,39; GFI = 0,93; AGFI = 0,86; CFI = 0,91; RMSEA = 0,11 (IC90% = 0,080 - 0,140); ECVI = 0,488 e CAIC = 174,39], showing evidence that there is the expression of a subtle prejudice against schizophrenia. It was also verified that the stereotype of dangerousness and the religious and psychological causal beliefs were the ones that explained the flagrant prejudice. It was also observed that stereotypes of dangerousness, attribution of penalty and disability predict subtle prejudice, as well as religious causal beliefs. With this, it is concluded that it is fundamental to work against prejudice that involves values, social norms and the culture of the Brazilian nation, considering the prejudice as produced and sustained by broader and more complex ideological webs that need to be transformed in order to a truly more just and egalitarian society